2011
DOI: 10.1039/c0lc00494d
|View full text |Cite
|
Sign up to set email alerts
|

A μL-scale micromachined microbial fuel cell having high power density

Abstract: We report a MEMS (Micro-Electro-Mechanical Systems)-based microbial fuel cell (MFC) that produces a high power density. The MFC features 4.5-μL anode/cathode chambers defined by 20-μm-thick photo-definable polydimethylsiloxane (PDMS) films. The MFC uses a Geobacter-enriched mixed bacterial culture, anode-respiring bacteria (ARB) that produces a conductive biofilm matrix. The MEMS MFC generated a maximum current density of 16,000 μA cm(-3) (33 μA cm(-2)) and power density of 2300 μW cm(-3) (4.7 μW cm(-2)), both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 43 publications
1
109
0
Order By: Relevance
“…There are other findings which similarly suggest that oxygen leakage into an MFC reduces power generation by pure cultures. Choi et al (8) found that power generation by G. sulfurreducens was enhanced when L-cystine (a chemical oxygen scavenger) was added into a microsized MFC (ferricyanide catholyte). While oxygen leakage through the cathode is well known (6,7,16,17), Yang et al (30) have shown that there is substantial oxygen leakage through the gaskets and septa used in these single-chamber, cubetype MFCs used in many studies (11,12,16,17,28).…”
mentioning
confidence: 99%
“…There are other findings which similarly suggest that oxygen leakage into an MFC reduces power generation by pure cultures. Choi et al (8) found that power generation by G. sulfurreducens was enhanced when L-cystine (a chemical oxygen scavenger) was added into a microsized MFC (ferricyanide catholyte). While oxygen leakage through the cathode is well known (6,7,16,17), Yang et al (30) have shown that there is substantial oxygen leakage through the gaskets and septa used in these single-chamber, cubetype MFCs used in many studies (11,12,16,17,28).…”
mentioning
confidence: 99%
“…In addition, the maximum areal power density (normalized to the geometric surface area of N‐GA, 9.4 cm 2 ) for N‐GA MFC is 1990.8 ± 106.1 mW m −2 , which is much higher than the values of CC MFC (78.2 ± 2.7 mW m −2 ) and rGO‐Ni MFC (517.6 ± 8.0 mW m −2 ). Significantly, the maximum areal power density is also among the state‐of‐the‐art performance and considerably higher than other MFCs with carbon‐based bioanodes, including the MEMS MFC (47 mW m −2 ),23 carbon nanotube‐based MFC (830 ± 10 mW m −2 )24 and graphene/PANI foam‐based MFC (768 mW m −2 ) 25. From the polarization curves shown in Figure 3b, the N‐GA MFC also exhibited the highest open circuit potential (0.69 ± 0.01 V) with the largest maximum current (20.50 ± 0.35 mA) among the three MFCs.…”
Section: Resultsmentioning
confidence: 94%
“…Shewanella oneidensis uses a solid component (known as nanowire) in the biofilm matrix that is conductive for electron transfer between the microbes and the electrode while Pseudomonas aeruginosa produces soluble electron shuttle that uses diffusive transport to carry electrons from the bacteria to the electrode. Therefore, Pseudomonas aeruginosa cannot produce high current density, because the diffusion rates of the mediators significantly limit the rate of EET by diffusion [10,11].…”
Section: B Current Generation and Light Responsementioning
confidence: 99%